Muscle Homeostasis and Regeneration From Molecular Mechanisms to Therapeutic Opportunities - Musarò, Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The book is a collection of original research and review articles addressing the intriguing field of the cellular and molecular players involved in muscle homeostasis and regeneration. One of the most ambitious aspirations of modern medical science is the possibility of regenerating any damaged part of the body, including skeletal muscle. This desire has prompted clinicians and researchers to search for innovative technologies aimed at replacing organs and tissues that are compromised. In this context, the papers, collected in this book, addressing a specific aspects of muscle homeostasis and regeneration under physiopathologic conditions, will help us to better understand the underlying mechanisms of muscle healing and will help to design more appropriate therapeutic approaches to improve muscle regeneration and to counteract muscle diseases.